1995
DOI: 10.1016/8756-3282(95)97366-n
|View full text |Cite
|
Sign up to set email alerts
|

Growth in infancy and bone mass in later life

Abstract: Objective-To examine the association between weight in infancy and bone mass during the seventh decade of life in a population based cohort for which detailed birth and childhood records were preserved. Methods-189 women and 224 men who were aged 63-73 years and were born in East Hertfordshire underwent bone densitometry by dual energy x ray absorptiometry. Measurements were also made of serum osteocalcin and urinary excretion of type 1 collagen cross linked N-telopeptide. Results-There were statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 12 publications
10
86
1
3
Order By: Relevance
“…A prenatal intake of 36% ethanolderived calories reduced fetal body weight in previous studies (10,11). Some studies found that low birth weight and deficient fetal bone development resulted in lower peak bone mass and an increased risk of future osteoporosis (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…A prenatal intake of 36% ethanolderived calories reduced fetal body weight in previous studies (10,11). Some studies found that low birth weight and deficient fetal bone development resulted in lower peak bone mass and an increased risk of future osteoporosis (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…With peak bone mass as a key stage in skeletal development prior to the onset of the natural process of age associated bone loss, determination of the relationship between birth weight and bone mass in early adulthood is imperative. Although numerous studies have been performed [18,19,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], only a limited number involved women around the third decade and these generally employed small sample sizes. Hence the findings of our study enhances current knowledge and supports the idea of invoking preventive measures while parental awareness may be warranted for those with or at risk of lower birth weights.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of birth weight on bone mass at older ages (>60 years) is less clear [19], while studies in younger individuals indicate that birth weight effects are more pronounced for BMC than BMD [13,20].…”
Section: Introductionmentioning
confidence: 96%
“…This results in permanent reduction in peak skeletal proportions attained later in life. Thus, several studies have shown that body weight in infancy is positively associated with adult bone mass (Cooper et al, 1997). Low rate of childhood growth has been associated with increased risk of hip fracture later in life .…”
Section: ) Consequences Of Alterations In Growth Hormone and Glucocomentioning
confidence: 99%